Inkheart - Funke, Cornelia, 1958-; Bell, Anthea (Frome, U.K. : Chicken House, 2004)
Twelve-year-old Meggie learns that her father, who repairs and binds books for a living, can'read' fictional characters to life when one of those characters abducts them and tries to force him into service.
Translation of: Tintenherz.
Originally published: Hamburg, Germany : C. Dressler Verlag, 2003.
Keywords: Books and reading -- Juvenile fiction; Characters and characteristics in literature -- Juvenile fiction; Magic -- Juvenile fiction